Prove the difference formula for tangent: Show that \( \tan(a - b) = \frac{\tan(a) - \tan(b)}{1 + \tan(a)\tan(b)} \).
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To prove the difference formula for tangent, we start with the sine and cosine definitions of tangent: \[ \tan(a - b) = \frac{\sin(a - b)}{\cos(a - b)} \] Using the sine and cosine difference identities: \[ \sin(a - b) = \sin(a)\cos(b) - \cos(a)\sin(b) \] \[ \cos(a - b) = \cos(a)\cos(b) + \sin(a)\sin(b) \] Now substituting these into the tangent formula: \[ \tan(a - b) = \frac{\sin(a)\cos(b) - \cos(a)\sin(b)}{\cos(a)\cos(b) + \sin(a)\sin(b)} \] Next, we can express \(\sin(a)\) and \(\sin(b)\) in terms of \(\tan(a)\) and \(\tan(b)\): \[ \sin(a) = \tan(a) \cos(a), \quad \sin(b) = \tan(b) \cos(b) \] Now substitute these into the expressions for \(\tan(a - b)\): After substituting and simplifying the expressions, we arrive at: \[ \tan(a - b) = \frac{\tan(a)\cos(a)\cos(b) - \tan(b)\cos(a)\cos(b)}{\cos(a)\cos(b) + \tan(a)\tan(b)\cos(a)\cos(b)} \] Factoring out common terms: This simplifies down to: \[ \tan(a - b) = \frac{\tan(a) - \tan(b)}{1 + \tan(a)\tan(b)} \] Thus, we have proved the difference formula for tangent: \[ \tan(a - b) = \frac{\tan(a) - \tan(b)}{1 + \tan(a)\tan(b)} \]